Pengaruh Gaya Kepemimpinan Transformasional dan Kepuasan Kerja Terhadap Quiet Quitting serta Dampaknya pada Kinerja Pegawai Dinas Pemuda dan Olahraga Kota Jambi - Ratu Rahmadilla Utama; Shofia; Besse Wediawati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of transformational leadership style and job satisfaction on quiet quitting and its impact on employee performance at the Youth and Sports Office of Jambi City. This research employs a quantitative approach with an explanatory causality design. The population consists of 38 Civil Servants (PNS and PPPK) at the Youth and Sports Office of Jambi City, with the entire population used as the sample (saturated sampling). Data collection was conducted through questionnaires using a Likert scale of 1–5. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results indicate that job satisfaction has a positive and significant effect on quiet quitting and employee performance. Quiet quitting has a significant effect on employee performance. Quiet quitting is able to mediate the effect of job satisfaction on employee performance. However, transformational leadership style does not have a significant effect on quiet quitting, nor on employee performance, and quiet quitting is unable to mediate the effect of transformational leadership on employee performance. This research contributes to the development of human resource management theory, particularly regarding the phenomenon of quiet quitting in the public sector.